Tool Use in Computer-Based Learning Environments: Adopting and Extending the Technology Acceptance Model. (11th February 2014) - Juarez Collazo, N. A.; Wu, X.; Elen, J.; Clarebout, G.
Abstract : This study adopts the Technology Acceptance Model (TAM) and extends it to study the effects of different variables on tool use. The influence of perceptions on tool use was studied in two different conditions: with and without explanation of the tool functionality. As an external variable, self-efficacy was entered in the TAM and the main research question thus focused on the mediating effects of perceptions (perceived tool functionality and perceived tool usability) between self-efficacy on the one hand and quantity and quality of tool use on the other. Positive effects of perceived usability on perceived functionality were hypothesized as well as positive effects of quantity and quality of tool use on performance. Positive effects were expected in the condition with explanation of the tool functionality. Ninety-three university students were provided with concept maps as the learning tools within a hypertext. Using path analysis, we found—similar to the TAM—a significant positive relationship between perceived usability and perceived functionality. Whereas perceived usability had a positive influence on the quantity of tool use, which positively influenced performance, perceived functionality had a negative influence on quantity of tool use. Self-efficacy showed a relationship with perceived usability only with the explained functionality condition.